Cody

Solution 1929456

Submitted on 10 Sep 2019 by 3-2
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

Test Suite

Test Status Code Input and Output
1   Pass
x = (1:5)'; y_correct = [1 5 4 3 2;2 1 5 4 3;3 2 1 5 4;4 3 2 1 5;5 4 3 2 1]; assert(isequal(shifted(x),y_correct))

y = 1 2 3 4 5 u = 5 1 2 3 4 y = 1 5 2 1 3 2 4 3 5 4 x = 5 1 2 3 4 u = 4 5 1 2 3 y = 1 5 4 2 1 5 3 2 1 4 3 2 5 4 3 x = 4 5 1 2 3 u = 3 4 5 1 2 y = 1 5 4 3 2 1 5 4 3 2 1 5 4 3 2 1 5 4 3 2 x = 3 4 5 1 2 u = 2 3 4 5 1 y = 1 5 4 3 2 2 1 5 4 3 3 2 1 5 4 4 3 2 1 5 5 4 3 2 1 x = 2 3 4 5 1

2   Pass
x = (1:3)'; y_correct = [1 3 2;2 1 3;3 2 1]; assert(isequal(shifted(x),y_correct))

y = 1 2 3 u = 3 1 2 y = 1 3 2 1 3 2 x = 3 1 2 u = 2 3 1 y = 1 3 2 2 1 3 3 2 1 x = 2 3 1

3   Pass
x = (1:4)'; y_correct = [1 4 3 2;2 1 4 3;3 2 1 4;4 3 2 1]; assert(isequal(shifted(x),y_correct))

y = 1 2 3 4 u = 4 1 2 3 y = 1 4 2 1 3 2 4 3 x = 4 1 2 3 u = 3 4 1 2 y = 1 4 3 2 1 4 3 2 1 4 3 2 x = 3 4 1 2 u = 2 3 4 1 y = 1 4 3 2 2 1 4 3 3 2 1 4 4 3 2 1 x = 2 3 4 1

4   Pass
x = (1:7)'; y_correct = [1 7 6 5 4 3 2;2 1 7 6 5 4 3;3 2 1 7 6 5 4;... 4 3 2 1 7 6 5;5 4 3 2 1 7 6; 6 5 4 3 2 1 7; 7 6 5 4 3 2 1]; assert(isequal(shifted(x),y_correct))

y = 1 2 3 4 5 6 7 u = 7 1 2 3 4 5 6 y = 1 7 2 1 3 2 4 3 5 4 6 5 7 6 x = 7 1 2 3 4 5 6 u = 6 7 1 2 3 4 5 y = 1 7 6 2 1 7 3 2 1 4 3 2 5 4 3 6 5 4 7 6 5 x = 6 7 1 2 3 4 5 u = 5 6 7 1 2 3 4 y = 1 7 6 5 2 1 7 6 3 2 1 7 4 3 2 1 5 4 3 2 6 5 4 3 7 6 5 4 x = 5 6 7 1 2 3 4 u = 4 5 6 7 1 2 3 y = 1 7 6 5 4 2 1 7 6 5 3 2 1 7 6 4 3 2 1 7 5 4 3 2 1 6 5 4 3 2 7 6 5 4 3 x = 4 5 6 7 1 2 3 u = 3 4 5 6 7 1 2 y = 1 7 6 5 4 3 2 1 7 6 5 4 3 2 1 7 6 5 4 3 2 1 7 6 5 4 3 2 1 7 6 5 4 3 2 1 7 6 5 4 3 2 x = 3 4 5 6 7 1 2 u = 2 3 4 5 6 7 1 y = 1 7 6 5 4 3 2 2 1 7 6 5 4 3 3 2 1 7 6 5 4 4 3 2 1 7 6 5 5 4 3 2 1 7 6 6 5 4 3 2 1 7 7 6 5 4 3 2 1 x = 2 3 4 5 6 7 1

5   Pass
x = (1:6)'; y_correct = [1 6 5 4 3 2;2 1 6 5 4 3;3 2 1 6 5 4;... 4 3 2 1 6 5;5 4 3 2 1 6; 6 5 4 3 2 1]; assert(isequal(shifted(x),y_correct))

y = 1 2 3 4 5 6 u = 6 1 2 3 4 5 y = 1 6 2 1 3 2 4 3 5 4 6 5 x = 6 1 2 3 4 5 u = 5 6 1 2 3 4 y = 1 6 5 2 1 6 3 2 1 4 3 2 5 4 3 6 5 4 x = 5 6 1 2 3 4 u = 4 5 6 1 2 3 y = 1 6 5 4 2 1 6 5 3 2 1 6 4 3 2 1 5 4 3 2 6 5 4 3 x = 4 5 6 1 2 3 u = 3 4 5 6 1 2 y = 1 6 5 4 3 2 1 6 5 4 3 2 1 6 5 4 3 2 1 6 5 4 3 2 1 6 5 4 3 2 x = 3 4 5 6 1 2 u = 2 3 4 5 6 1 y = 1 6 5 4 3 2 2 1 6 5 4 3 3 2 1 6 5 4 4 3 2 1 6 5 5 4 3 2 1 6 6 5 4 3 2 1 x = 2 3 4 5 6 1